EXTRALINGUISTIC CONTEXT ROLES IN DETERMINING MEANINGS OF JAVANESE PHATIC EXPRESSION MBOTEN: A SOCIOPRAGMATIC PERSPECTIVE - Kunjana Rahardi (International Journal of Humanity Studies (IJHS), 2019)
The indirect expression of intention in the Javanese culture-based speech community requires the speaker and the hearer to understand the importance of contexts in communication. Failure to understand the context of interaction will definitely impede communication and interaction, or even worse it may cause misunderstanding in the communication and interaction process. In the Javanese speech community, people may say mboten or no without intending to negate or to express falsity. On the contrary, people may say inggih or yes which does not necessarily mean to affirm or to express an assertion. Therefore, it is clear that in the Javanese speech community, the extralinguistic contexts in the communication is very important and defines the purpose of utterances. Based on the research background, the research on extralinguistic contexts to determine the meaning of mboten was carried out. The objective of the research was to elaborate the extralinguistic contexts which determine the meaning of mboten. The data consists of excerpts containing Javanese phatic mboten. The technique of collecting data was recording and note-taking. Besides, interview or speaking method was employed to gather the data. The data analysis was done using the distributional and content analysis methods. This research results in five functions of extralinguistic contexts to determine the meaning of the utterance. The five functions are: (1) the extralinguistic contexts to affirm the intention of negation; (2) the extralinguistic context as the background of negation; (3) the extralinguistic contexts to confirm the meaning of negation; (4) the extralinguistic contexts to affirm the intention of negation; (5) the extralinguistic contexts to affirm the phatic function. The result of the research is very important and contributes significantly to the development of linguistics, especially the development of pragmatics embedded in culture-specific concepts.